2015
DOI: 10.1002/chem.201405991
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear Ruthenium(II) Complexes That Induce and Stabilise G‐Quadruplex DNA

Abstract: A series of dinuclear ruthenium(II) complexes were synthesised, and the complexes were determined to be new highly selective compounds for binding to telomeric G-quadruplex DNA. The interactions of these complexes with telomeric G-quadruplex DNA were studied by using circular dichroism (CD) spectroscopy, fluorescence resonance energy transfer (FRET) melting assays, isothermal titration calorimetry (ITC) and molecular modelling. The results showed that the complexes 1, 2 and 4 induced and stabilised the formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 72 publications
0
29
0
Order By: Relevance
“…The treatment of cervical cancer faces one of the most challenging problems in clinical oncology in that there are few effective treatments to block the metastasis of cervical cancer cells. [12][13][14][15] Ruthenium complexes have always been regarded as some of the most potential antitumour inhibitors owing to their decent antitumour activity [16][17][18][19][20] and low toxicity. [21][22][23][24] A number of Ru complexes have been designed and their anti-metastasis activities against various tumours have been investigated extensively.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of cervical cancer faces one of the most challenging problems in clinical oncology in that there are few effective treatments to block the metastasis of cervical cancer cells. [12][13][14][15] Ruthenium complexes have always been regarded as some of the most potential antitumour inhibitors owing to their decent antitumour activity [16][17][18][19][20] and low toxicity. [21][22][23][24] A number of Ru complexes have been designed and their anti-metastasis activities against various tumours have been investigated extensively.…”
Section: Introductionmentioning
confidence: 99%
“…Such G4 forming sequences have been reported to be prevalent in genomes, such as immunoglobulin switch regions and promoter regions of oncogenes and telomere ends 4, 5 , as well as in particular RNA domains, such as the first introns, 5′- and 3′- untranslated regions, telomeric RNA 6 , and the genomic RNA of Zika virus replication 7 . Accumulating evidence has suggested that G4s play an intrinsic role in gene expression 814 .…”
Section: Introductionmentioning
confidence: 99%
“…[21] They demonstratedt he ability of this NDI-phenolate conjugate to kill MCF7 cancer cells after irradiation.The design of new metal complexes targeting G-quadruplex DNA has attracted intense interestw ithr egard to their potential anticancer properties. [22,23] Indeed, some Pt II , [24][25][26][27][28] Ni II , [29][30][31] Ru II , [32][33][34] and Ir III complexes [35][36][37] have shown good affinity and selectivity towards G4s. In comparison to organic compounds, metal complexeshave many advantages, such as anet positive charge,t unable geometry,a nd, most interestingly,s ome of them display potentially useful photochemical properties.…”
mentioning
confidence: 99%